Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/app9173594
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Effect of Space-Arrangement and Wall Thermal Resistance on Indoor Thermal Environment of Passive Solar Single-Family Building in Tibet

Abstract: In areas where solar energy is abundant, such as the Tibetan plateau, passive solar buildings are attracting more and more attention and becoming a popular form of rural building. However, it is often difficult to achieve the satisfactory indoor thermal environment in a local rural passive solar single-family house. In order to improve the indoor thermal environment of passive solar buildings through building design, a systematic study of rural single-family buildings in Tibet was conducted. The basic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…us, it is an important measure to reduce building energy consumption and improve the indoor thermal environment by optimizing the thermal design and structural design of external walls. So far, many scholars have conducted research on the energysaving structure design of the wall [28][29][30][31] and indicated that indoor thermal environment quality can be effectively improved, and building energy consumption can be significantly reduced if external walls can be rationalized in design and construction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…us, it is an important measure to reduce building energy consumption and improve the indoor thermal environment by optimizing the thermal design and structural design of external walls. So far, many scholars have conducted research on the energysaving structure design of the wall [28][29][30][31] and indicated that indoor thermal environment quality can be effectively improved, and building energy consumption can be significantly reduced if external walls can be rationalized in design and construction.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the heat transfer coefficient of the wall with different orientations is considered to be the constant in building thermal design [31,32]. Nevertheless, for some areas with high solar radiation intensity, the solar radiation intensity varies greatly in different orientations [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, everything has been said on that topic? Not at all, and up-to-date research on all aspects related to the design of a zero-energy building is still being developed, as the articles reported [1][2][3][4][5][6][7][8][9][10][11] in this special issue testify.…”
mentioning
confidence: 99%
“…In fact, the reader will find in the following papers, some works at the level of the component-such as the one of Memon et al [2] that studies the performance of a triple vacuum glazing, the one of Viljanen and Lu [6] on the moisture performance of highly insulated walls, the one of Dong et al [5] on the energy savings potential of cross-laminated timber constructions, and the study of passive solar systems by Cui et al [11]-and the others at the level of the building. Two works (Ruiz et al [3] and Ferrara et al [8]) treat the problem of the integration of renewable sources within a ZEB.…”
mentioning
confidence: 99%